A Prospective Comparative Study of Fracture Distal End Radius Treated by K Wire Vs Plating - Sharma, Kushal; Manish, Manish; P Bhore, Emmanuel; Pahadiya, Anshul Kumar (Journal of Neonatal Surgery, 2025)
Background: The aim of this study was to compare the radiological and functional outcomes of 100 patients who underwent K-wire fixation vs Plating for fractures of the distal end radius. Methods: Study was conducted between August 2022 to March 2024, patients with distal end radius fractures were included in the study and managed with percutaneous intramedullary K-wire fixation VS Plating. A total of 100 patients who met the inclusion criteria for the study were treated with this modality. Results: The mean values for volar tilt, radial inclination, radial length and ulnar variance were all significantly better in the volar plate group. According to MAYO Wrist score, in Plating out of 50 patients, 38 had excellent outcomes and 12 had good outcomes while in K wire out of 50 patients, 30 patients had excellent outcomes, 15 had good outcomes, 3 had fair and 2 had poor outcomes, so this shows that Plating is superior than K wire in distal end radius fractures. K-wire fixation and plating are effective for distal radius fractures, plating may offer superior outcomes in terms of recovery and stability. Conclusions: From this study, we conclude that Plating is a reliable implant for distal end radius fractures, leading to a high rate of bone union, restoring the anatomical alignment and reducing the chance of implant failure or deformities as compared to K wire.